1975
DOI: 10.1055/s-0028-1106344
|View full text |Cite
|
Sign up to set email alerts
|

Untersuchungen über das Verhalten der Androgene im Plasma hirsuter Frauen

Abstract: 109 women with hirsutism were investigated (102 with idiopathic hirsutism, four with Stein-Leventhal syndrome, one each with adrenal adenoma, adrenal carcinoma and hilus-cell tumour). Levels of testosterone, dihydrotestosterone, androstenediol and dehydroepiandrosterone were measured, usually in the course of a combined adrenal-ovarian stimulation-suppression test. Measuring several plasma androgens made it possible to distinguish idiopathic hirsutism from other endocrine diseases with hirsutism. Mean plasma t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

1975
1975
1980
1980

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 3 publications
(3 reference statements)
1
1
0
Order By: Relevance
“…This DHT precursor, which is mainly secreted by the adrenal cortex, and which is not suppressed by fluoxymesterone, probably explains why DHT is suppressed to a smaller degree than T. The DHT increase we found was not significantly smaller than that of after HCG stimulation. This is in agree¬ ment with the observation of Demisch et al (1971) and of Maurer et al (1973).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…This DHT precursor, which is mainly secreted by the adrenal cortex, and which is not suppressed by fluoxymesterone, probably explains why DHT is suppressed to a smaller degree than T. The DHT increase we found was not significantly smaller than that of after HCG stimulation. This is in agree¬ ment with the observation of Demisch et al (1971) and of Maurer et al (1973).…”
Section: Discussionsupporting
confidence: 94%
“…Thus it was not surprising that plasma DHT and showed a significant correlation (Gupta et al 1972) and that DHT showed a similar increase as after HCG stimulation (Demisch et al 1971;Maurer et al 1973). This paper is concerned with the relationship between DHT and in the peripheral plasma of normal adult males.…”
mentioning
confidence: 73%